In vitro maturation of Nelore breed (Bos taurus indicus) oocytes using either purified porcine FSH or recombinant human FSH: results from a large-scale in vitro embryo production routine - Martins, Leticia Prates; Martinhão, Luany Alves Galvão; Grazia, João Gabriel Viana; Faria, Otavio Augusto Costa; Figueiredo, Ricardo Alamino; Viana, Joao Henrique Moreira (Frontiers in Veterinary Science, 2025)
IntroductionThis study evaluated whether porcine FSH (pFSH) could be replaced by follitropin-alpha, a recombinant human FSH (rhFSH), during in vitro maturation (IVM) of cumulus-oocyte complexes (COC) recovered from Nelore (Bos taurus indicus) cattle in a large-scale in vitro embryo production (IVP) program.MethodsWe performed three experiments, all using grade I COC (n = 10,208) submitted to IVM in TCM199 without FSH (-FSH, negative control) or supplemented with either 0.5 μg/mL pFSH (Folltropin-V) or 0.1 IU rhFSH (Gonal-F). The remaining procedures, media, and culture conditions for in vitro embryo production (IVP) were similar. In Exp. 1, COC (n = 2,791) were IVM in the absence of FSH (-FSH) or with pFSH or rhFSH, and underwent IVP. Blastocysts were assessed for hatching as fresh or after vitrification and warming. In Exp. 2, COC (n = 720) were IVM in groups -FSH, pFSH, or rhFSH, and the expanded blastocysts produced were stained with Hoechst 33342 and propidium iodide for total, trophoblast and ICM cell count. In Exp. 3, we used the same experimental design as in Exp. 1 but in a commercial IVP routine, which included the use of COC (n = 6,697) recovered both by OPU and from slaughterhouse, Y-sorted semen, and the transfer of part of the blastocysts produced.ResultsIn Exp. 1, blastocyst rates were greater (p < 0.05) in groups treated with than without FSH (39.3% and 40.6% vs 34.8% for pFSH, rhFSH and -FSH, respectively; p = 0.0244). However, there was no effect of treatment on hatching rates of fresh (74.5%, 79.0% and 70.1% for -FSH, pFSH, and rhFSH, respectively; p = 0.2621) or vitrified blastocysts (75.0%, 69.6% and 73.2% for -FSH, pFSH, and rhFSH, respectively; p = 0.7623). In Exp. 2, blastocysts from the rhFSH group presented more cells in the trophoblast (110.3±5.6 vs 80.0±5.7 and 878.4±5.1 for rhFSH, -FSH, and pFSH, respectively; P=0.0002), but not in the ICM (p = 0.3231), when compared with pFSH and -FSH groups. In Exp. 3, both pFSH and rhFSH increased cleavage (76.0% and 75.1% vs 71.6%, p = 0.0035) and blastocyst rates (38.1% and 39.5% vs 34.3%, p = 0.0102), but not pregnancy rate (43.8% and 33.3% vs 56.0%, p = 0.1080), compared with -FSH.DiscussionIn summary, follitropin-alpha is an alternative to pFSH as a medium supplement for IVM of bovine COC.